Efektivitas Penerapan Nilai Penjas Melalui Pembelajaran Daring Siswa Kelas Xi Sma Negeri 1 Kota Mungkid Kabupaten Magelang (Universitas Negeri Semarang, 2022)
This research is a quantitative research through a survey approach. The subjects of this study were students of SMA Negeri 1 Mungkid City. The sampling technique used was purposive sampling. Data collection techniques using observation and questionnaires. Processing data using a descriptive percentage formula.The results of the study show that in the application of physical education values ​​which include honesty values, 13.37% are in the very good category, 83.13% in the good category, 3.48% in the sufficient category, and 0% in the poor category. The application of caring values ​​was 8.13% in very good category, 73.25% in good category, 18.60% in sufficient category, and 0% in poor category. The application of fair value was 28.48% in the very good category, 52.90% in the good category, 18.60% in the sufficient category, and 0% in the poor category. The application of the value of responsibility is 50.00% in the very good category, 47.67% in the good category, 2.32% in the sufficient category, and 0% in the poor category. The application of the value of respect is 22.67% in the very good category, 71.51% in the good category, 5.81% in the sufficient category, and 0% in the poor category. The application of civilized values ​​was 3.48% in the very good category, 73.25% in the good category, 23.25% in the moderate category, and 0% in the poor category.Based on the results of the study, it can be concluded that the application of the positive value of physical education through online learning for class XI students of SMA Negeri 1 Mungkid City, Magelang Regency is running effectively.